Prospects for the formation of effective ecological and economic systems of water usage - Molchak, Yaroslav; Myskovets, Iryna; Horbach, Ludmila (Human Geography Journal, 2021)
The article deals with defining the essence, methods and techniques of the research of ecological and economic problems of water usage, assessments of water and resource potential as to the region. The subject of this study is the environmental and economic problems of water supply. The object that is determined in the article is the water resource and eco-economic potential of Volyn region. The purpose of the study is the ecological and economic assessment the prospects of water supply, socio-economic development of the region. In accordance with the purpose, the following tasks are set and solved in the study: analyzing current state of ecological and economic water supply of the region; taking into account the water factor in the forecasts of economic development of the region; solving the ways of eco-economic problems of water supply to the territories. Modern problems such as rational usage, protection and reproduction of water resources are considered. Changes in the ecological and economic systems of water usage in the Volyn region in the market conditions are analyzed. The issue of protection, complex usage and restoration the balance of environment is considered. It is the leading point in the ecological, economic, political and social life not only of peculiar countries, but also of the entire continents. Under the influence of economic activity, natural landscapes are changed. Progressive pollution of human habitat has led to a deterioration in quality of life, negatively affected demographic characteristics. The ecological aspect of VGK development provides a set of measures to ensure the protection of water resources and rational usage of water; increasing safety when it comes to usage of chemicals; solving the problem of waste. Based on results of the conducted research we can conclude that, the great importance of water resources in the development of the national economy not only of Volyn region, but the country as a whole is extremely important. The problem of balanced environmentally safe water usage and dynamic development of the water complex of Ukraine is critical. The nature and types of usage of natural waters are highly diverse and multifaceted. Water is used almost in all areas of the economy and aspects of human life. The extreme importance of such natural resource as a water and its transformation into a factor determining the development of society, resulted to the problem of rational use and protection of the aquatic environment. The main directions of solving ecological and economic problems of water supply of the territories are offered.